A Requiem for Peacebuilding?
XI, 247 p. 6 illus., 3 illus. in color.
Keywords: Barbara Segaert is Project Coordinator at the University Centre Saint-Ignatius Antwerp, Belgium, where she develops academic programmes on various topics of contemporary relevance to society. Jorg Kustermans is Associate Professor of International Relations in the Department of Political Science at the University of Antwerp, Belgium. He does research on the conceptual history of peace and on the shifting sources of international authority. Tom Sauer is Associate Professor in International Politics at the University of Antwerp, Belgium. He is specialized in international security, and more in particular in nuclear arms control, proliferation, and disarmament. He is a former BCSIA Fellow at Harvard University, USA. Sauer received the 2019 Rotary International Alumni Global Service Award. This book assesses the claim that peacebuilding is a moribund international practice. Its contributors trace the origins of peacebuilding, bring back to memory its moments of triumph, and reflect on the reports of its decline. The story of peacebuilding parallels the broader story of liberalism’s rise and fall in world politics, including the attempt to remedy an ailing patient by administering a magic medicine – “the local turn”. Its contributors further write about what may come after peacebuilding as we still know it. They describe more locally rooted attempts at building peace and how they operate in the shadows of, and in an ambiguous relationship with, governmental and international peacebuilders. The book finally suggests that reports of the pending death of peacebuilding are probably premature. Peacebuilding is a resilient international practice, apt to adjust itself to a changing environment, and too important a source of legitimacy for those that wield power. .